Impact of the implementation of management systems of projects in contractors residential gas in bogotá (Ingenio Magno, 2018)
Household gas contracting companies are part of Colombian gas guild, which help the encouragement, development and economic growth and productive capacity of the country. This kind of companies require the implementation of a project management system what allows them to reorganize their processes internally, in order to improve the provision of their services, facilitating the continuity of their contracts with the regulatory entity, which in Colombia is Gas Natural Fenosa. The project management system has become a mandatory factor for the contractor companies, to comply with the requirements and regulatory requirements directly demanded by the superintendence industry and commerce and which directly affect consumers who are provides the household gas service in Bogotá - Colombia, being pertinent to clarify that as evidenced in this article, having a certified management system is not a guarantee that a project management system is being complied with. The purpose of this document is to show the impact that the process of implementation of the project management system has had on household gas contractors in Bogotá, which were not clear initially about how to measure the productivity or profitability of their business.
Keywords: Management System; Natural Gas; Project; Contractors; Productivity